THE IMPACT OF SOCIAL MEDIA ON THE WAY TEENS SOCIALIZE IN THE GLOBAL ERA - Aisyah Kurnia Putri; Ainaa Farah Sulaiman; Adibah Safira; Alghaisya Naurah Hardin; Abdur Rasyid Humaidi; Andi Irawan (CV. Radja Publika, 2025)
The rapid development of information technology has brought changes in the culture of Indonesian society.. It cannot be denied that the impact of the Industrial Revolution 4.0 cannot be avoided with the presence of the internet.. Social mediaSocial media provides individuals with the tools they need to build online identities, interact with others, and build social networks. This study aims to discuss the impact of social media on how teenagers socialize in the global era.This research uses qualitative methods through literature review and in-depth interviews. The literature review includes scientific articles, reports, and previous research findings. This research indicates that social media hasimpactsignificantly impacts adolescents' lifestyles and social interactions. Social media introduces global trends, shapes self-identity, and creates new social patterns that expand opportunities for friendship but also pose challenges in the context of mental health and social anxiety.